2006
DOI: 10.1002/eji.200535202
|View full text |Cite
|
Sign up to set email alerts
|

Macrophage and T lymphocyte apoptosis during experimental pulmonary tuberculosis: their relationship to mycobacterial virulence

Abstract: The kinetics of macrophage and T lymphocyte apoptosis were determined in a wellcharacterized mouse model of pulmonary tuberculosis, comparing strains of intermediate (H37Rv) and high virulence (Beijing strain, code 9501000). Both strains induced a high percentage of apoptotic activated macrophages at days 1 and 3 post infection, although this was twofold lower in Beijing-infected mice. Progressive pneumonia started at day 14 (Beijing) or 21 (H37Rv) post infection. Pneumonic areas contained numerous macrophages… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
51
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(54 citation statements)
references
References 25 publications
3
51
0
Order By: Relevance
“…However, FasL mRNA was higher in both CD14 1 and CD14 À cells from TB patients, suggesting a broad upregulation of this molecule in this cohort. This observation is consistent with earlier reports from human and murine M. tuberculosis infections [38,40,[42][43][44]. …”
supporting
confidence: 93%
See 1 more Smart Citation
“…However, FasL mRNA was higher in both CD14 1 and CD14 À cells from TB patients, suggesting a broad upregulation of this molecule in this cohort. This observation is consistent with earlier reports from human and murine M. tuberculosis infections [38,40,[42][43][44]. …”
supporting
confidence: 93%
“…In addition to its role as an activating factor, TNF-a plays an important role in immunopathology [39] and cell death [40]. Cell death by apoptosis has been postulated as a potentially important method by which infected macrophages are removed in TB [41].…”
Section: Assessment Of Production Of Fas and Fasl In Different Clinicmentioning
confidence: 99%
“…Bcl2 is involved in suppressing apoptosis and it has been implicated in apoptosis associated with infections; however, this gene was found outside the critical candidate region for Ity3 (Kroemer 1997;Rios-Barrera et al 2006).…”
Section: Resultsmentioning
confidence: 99%
“…It has been suggested that macrophage apoptosis represents a successful host immune response to M. tuberculosis infection in vivo (40,42). M. tuberculosis is an intracellular pathogen and, as such, this organism is dependent on the continuing survival of the host cell to provide it with a refuge in which to replicate.…”
Section: Discussionmentioning
confidence: 99%